Vitamin D3 deficiency induced intestinal inflammatory response of turbot through nuclear factor-κB/inflammasome pathway, accompanied by the mutually exclusive apoptosis and autophagy - Chen, Zhichu; Huang, Dong; Yongyut, Prakaiwan; Li, Guangbin; Esteban, María Ángeles; Jintasataporn, Orapint; Deng, Junming; Zhang, Wenbing; Ai, Qinghui; Mai, Kangsen; Zhang, Yanjiao (Frontiers in Immunology, 2022)
Vitamin D3 (VD3) participated widely in the nuclear factor-κB (NF-κB)-mediated inflammation, apoptosis, and autophagy through the vitamin D receptor (VDR). However, the molecular mechanisms remain not understood in teleost. The present study investigated the functions of VD3/VDR on intestinal inflammation, autophagy, and apoptosis of turbot in vivo and in vitro. Triple replicates of 30 fish were fed with each of three diets with graded levels of 32.0 (D0), 1012.6 (D1), and 3978.2 (D2) IU/kg VD3. Obvious intestinal enteritis was observed in the D0 group and followed with dysfunction of intestinal mucosal barriers. The intestinal inflammatory response induced by VD3 deficiency was regulated by the NF-κB/inflammasome signalling. The promotion of intestinal apoptosis and suppression of intestinal autophagy were also observed in the D0 group. Similarly, VD3 deficiency in vitro induced more intense inflammation regulated by NF-κB/inflammasome signalling. The mutually exclusive apoptosis and autophagy were also observed in the group without 1,25(OH)2D3in vitro, accompanied by similar changes in apoptosis and autophagy increased apoptosis. The gene expression of VDRs was significantly increased with the increasing VD3 supplementation both in vivo and in vitro. Moreover, VDR knockdown in turbot resulted in intestinal inflammation, and this process relied on the activation of inflammasome mediated by NF-κB signalling. Simultaneously, intestinal apoptosis was promoted, whereas intestinal autophagy was inhibited. In conclusion, VD3 deficiency could induce intestinal inflammation via activation of the NF-κB/inflammasome pathway, intestinal apoptosis, and autophagy formed a mutually exclusive relation in teleost. And VDR is the critical molecule in those processes.